Expression and significance of MOC‐31 and calretinin in pleural fluid of patients with lung cancer. Issue 7 (24th October 2014) - Lv, Ming; Leng, Ji‐Hong; Hao, Yan‐Yong; Sun, Yan; Cha, Na; Wu, Guang‐Ping
<x xml:space="preserve">Abstract</x> Background The cytologic assessment of pleural effusions to distinguish carcinoma cells from reactive mesothelial cells is particularly challenging. The aim of this study was to investigate the diagnostic value of monoclonal antibody (MOC‐31) and calretinin in pleural fluid of patients with lung cancer to significantly improve the diagnostic accuracy. Methods The expressions of MOC‐31 and calretinin were detected by means of S‐P immunocytochemical technique in pleural effusions of patients with lung cancer (n = 92) and in patients with benign lung disease (n = 70). Results The positive rate of MOC‐31 in pleural fluid was 90.2% (83/92) from patients with lung cancer and 2.9% (2/70) from patients with benign lung diseases, showing a significant difference (P < 0.01). Calretinin was expressed 87.1% (61/70) in benign lung diseases and 6.5% (6/92) in lung cancer, also showing a significant difference (P < 0.01). The optimal combination for assay was MOC‐31 + calretinin: Sensitivity and specificity were 100 and 98.6%, respectively. Conclusion MOC‐31 and calretinin are of important clinical value for diagnosing and differentially diagnosing the cancer cells in pleural fluid of patients with lung cancer. Diagn. Cytopathol. 2015;43:527–531. © 2014 Wiley Periodicals, Inc.